PThe Pro-environmental Behavior of Nature-Based Tourists The Case of Alagol's International Lagoon - Arman Akhoondnejad; Bibi Sara Daz (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2017)
Nature-based tourism is one of the most important types of tourism that plays a very important role in the development of sustainable environments. One of the best practices for sustainable environmental development is to focus and improve the pro-environmental behavior of the tourist. Hence, this research explores the pro-environmental behavior of the tourist and empirically investigates the role of attachment to the place on tourist satisfaction. To this end, 286 domestic tourists who visited the international wetland of Alagol were surveyed using available sampling method. Using structural equation modeling through Liserl software, the results showed positive and significant effects of attachment to the location and tourist satisfaction on the pro-environmental behavior of tourist. The attachment to the place also had a positive and significant effect on the satisfaction of the tourists.